Two cases of recovery of occlusion by a combination of surgery and orthodontic therapy for adult mandibular impacted teeth. Issue 1 (1st June 2012) - Sato, Chu; Nomura, Joji; Matsumura, Yoshihiko; Kato, Hideharu; Yanase, Shigeaki; Tagawa, Toshiro
Abstract: We experienced 2 patients in which occlusion was successfully recovered by a combination of surgical subluxation and orthodontic therapy for adult mandibular impacted teeth. Of these cases, the tooth in one case was still vital after completion of the treatment. Herein, we report these 2 cases with a review of the literature.